Perception of patient safety culture among hospital staff - Stoyanova Rumyana; Dimova Rositsa; Tornyova Bianka; Mavrov Momchil; Elkova Harieta (Sciendo, 2021)
A patient safety culture (PSC) is a complex phenomenon, representing an essential part of the organizational culture and refers to the shared values, conceptions and beliefs which contribute to the formation and encouragement of safe behavioural models in a health organization. With this study, the authors wanted to delineate the attitude of hospital staff in Bulgaria regarding PSC and to document to whether attitudes differ between physicians and other healthcare professionals (HCPs).